2007
DOI: 10.7748/ns2007.01.21.17.35.c6394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating nurse consultants’ work through key informant perceptions

Abstract: This multi-site evaluative study is the result of work commissioned by a number of National Health Service (NHS) Trusts to evaluate the impact of the nurse consultant role. It explored the views of both stakeholders and nurse consultants and was conducted by Northumbria, Teesside and Bournemouth Universities and a number of their affiliated NHS Trusts. The evaluation was based on the '360 degree feedback process' and used case study methodology, inviting stakeholders or key informants, including clinical and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Certain personal characteristics, such as strength, creativity, dynamics, adaptability, and empathy, appear to be distinctive for these advanced‐level practitioners. These personal characteristics, combined with broad prior experience (Wood et al ., 1996; Manley, 1997; Dawson & McEwen, 2005; Woodward et al ., 2005; Wolf & Robinson‐Smith, 2007; Manley et al ., 2008), and an education “up to or beyond the master degree level” (Appel et al ., 1996; Wood et al ., 1996; Manley, 1997; Scott, 1999; Charters et al ., 2005; Dawson & McEwen, 2005; Woodward et al ., 2005; Jinks & Chalder, 2007; Redwood et al ., 2007; Wolf & Robinson‐Smith, 2007; Dawson & Coombs, 2008; Baldwin et al ., 2009), were identified as necessities for providing the skills and knowledge needed in the APN position (Manley, 1997). In comparison to their international colleagues, Australian CNC appear to have a lower level of education, and their career development is based more on their career history (Appel et al ., 1996; Vaughan et al ., 2005; O'Baugh et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Certain personal characteristics, such as strength, creativity, dynamics, adaptability, and empathy, appear to be distinctive for these advanced‐level practitioners. These personal characteristics, combined with broad prior experience (Wood et al ., 1996; Manley, 1997; Dawson & McEwen, 2005; Woodward et al ., 2005; Wolf & Robinson‐Smith, 2007; Manley et al ., 2008), and an education “up to or beyond the master degree level” (Appel et al ., 1996; Wood et al ., 1996; Manley, 1997; Scott, 1999; Charters et al ., 2005; Dawson & McEwen, 2005; Woodward et al ., 2005; Jinks & Chalder, 2007; Redwood et al ., 2007; Wolf & Robinson‐Smith, 2007; Dawson & Coombs, 2008; Baldwin et al ., 2009), were identified as necessities for providing the skills and knowledge needed in the APN position (Manley, 1997). In comparison to their international colleagues, Australian CNC appear to have a lower level of education, and their career development is based more on their career history (Appel et al ., 1996; Vaughan et al ., 2005; O'Baugh et al ., 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty‐seven articles discussed advanced clinical practice as a domain of APN. As the essence of the APN role is expert nursing practice, there appears to be unanimity about advanced clinical practice being the main or central domain of the role (McFadden & Miller, 1994; Wood et al ., 1996; Scott, 1999; Dawson & Spence, 2001; Vaughan et al ., 2005; Jinks & Chalder, 2007; Redwood et al ., 2007) comprising 23–50% of the advanced practice nurse's total working time (McFadden & Miller, 1994; Charters et al ., 2005; Darmody, 2005; Jinks & Chalder, 2007). However, Dawson and Coombs (2008) found that NC expert clinical practice has moved from high involvement to the lowest involvement in just a few years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent research on consultant practice developed in parallel with the project or subsequent to it; for example: the evaluation of consultant nurse/midwife roles ( Guest et al, 2001;Lathlean & Masterson, 2004;Redwood, 2007;McIntosh and Tolson, 2008); exploration of the role's complexity (Woodward et al, 2006;Jinks and Chalder, 2007;McIntosh and Tolson, 2008); leadership (Woodward et al, 2006;Lathlean, 2007;McIntosh and Tolson, 2008;Manley et al, 2008); and the role's impact on patients and/or across organisations (Ryan et al, 2006;Redwood, 2007;Avery and Butler, 2008). No other research focused on developing the facilitation skills of consultant practitioners or supporting aspiring consultants either prior to or since the study reported here.…”
Section: Background and Literaturementioning
confidence: 99%